Dell Education Services Topic-Based Learning: Using Topic-Based Learning (TBL) to Improve the Learning Experience for our Data Protection Certification eLearning Course - Cronquist, Bruce; Stone, Todd (International Journal of Advanced Corporate Learning (iJAC), 2020)
Traditional learning is often delivered as larger courses, requiring more development time, and containing substantial amounts of information. Often, that information is not relevant to the learner and, structured in poor sequence, isn't needed until later in the training (if it is even needed at all). Topic based learning, also often referred to as task-based learning, differs from traditional learning because it focuses on what the learner needs to do, versus what they should know. TBL focuses on providing need to know information, closer to the time of need. This case study shows how using Topic Based Learning, or TBL, improved the learning experience for our Data Protection Certification eLearning course. We’ll also show how it saved not only time for the learners but also time and resources for the Dell Technologies Education Services Department.